Photoionization of water molecules by high energy photons - Martini, Lara (2017)
We theoretically study the photoionization of water molecules by high energy photon impact. We develop a model in which the final state wave function is given by a Coulomb continuum wave function with effective charges and the water molecule bound states are represented using the Moccia’s monocentric wave functions. We obtain analytical expressions for the transition matrix element that enable the computation of cross sections by numerical quadratures. We compare our predictions for photon energies between 20 and 300 eV with more elaborated theoretical results and experiments. We obtain a very good agreement with experiments, in particular, at enough high energies where there is a lack of elaborated results due to their high computational cost.